Carbohydrate metabolism and cytology of S-type cytoplasmic male sterility in wheat - Ge, Shijie; Ding, Fugong; Daniel, Bimpong; Wu, Cuicui; Ran, Mingyang; Ma, Chi; Xue, Yuhang; Zhao, Die; Liu, Yike; Zhu, Zhanwang; Fang, Zhengwu; Zhang, Gaisheng; et al. (Frontiers in Plant Science, 2023)
Cytoplasmic male sterility (CMS) is an important tool for hybrid heterosis utilization. However, the underlying mechanisms still need to be discovered. An adequate supply of nutrients is necessary for anther development; pollen abortion would occur if the metabolism of carbohydrates were hampered. In order to better understand the relationship between carbohydrate metabolism disorder and pollen abortion in S-CMS wheat, the submicroscopic structure of wheat anthers was observed using light microscopy and transmission electron microscopy; chloroplast proteome changes were explored by comparative proteomic analysis; sugar measuring and enzyme assays were performed; and the expression patterns of carbohydrate metabolism-related genes were studied using quantitative real-time PCR (qRT-PCR) method. These results indicated that the anther and microspore in S-CMS wheat underwent serious structural damage, including premature tapetum degeneration, nutritional shortage, pollen wall defects, and pollen grain malformations. Furthermore, the number of chloroplasts in the anthers of S-CMS lines decreased significantly, causing abnormal carbohydrate metabolism, and disintegration of osmiophilic granules and thylakoids. Meanwhile, some proteins participating in the Calvin cycle and carbohydrate metabolism were abnormally expressed in the chloroplasts of the S-CMS lines, which might lead to chloroplast dysfunction. Additionally, several key enzymes and genes related to carbohydrate metabolism were significantly inhibited in S-CMS. Based on these results, we proposed a carbohydrate metabolism pathway for anther abortion in S-type cytoplasmic male sterility, which would encourage further exploration of the pollen abortion mechanisms for CMS wheat.